BUSINESS RISK, EFFICIENCY, AND QUALITY OF INVESTMENT DECISIONS - Axel Giovanni; Asri Khayati; Alifaa Jauzaa; Devi Wahyu Utami (Jurnal Ekonomi dan Manajemen, 2022)
The quality of investment decisions made by companies has a central role in supporting the achievement of maximizing shareholder value. This study aims to provide empirical evidence regarding the role of business risk and efficiency in explaining the variability of investment decision quality. The sample in this study includes all companies in the property, real estate, and building construction sectors from 2014 to 2018. The number of samples in this study were 62 companies with a research period of 5 years so that the total observations in this study were 320 observations. The analytical tool used is linear regression. The results of the study provide evidence of the importance of the role of business risk and efficiency in explaining the quality of the company's investment quality. In this case the business risk variable has a negative and significant effect on the quality of investment decisions and the efficiency variable has a positive and significant effect on quality of investment decisions.